2021
DOI: 10.1055/a-1354-5958
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Use of Handheld Point-of-Care Ultrasound (HH-POCUS) in Rural Brandenburg – A Pilot Study

Abstract: Purpose This study aims to evaluate the use of handheld ultrasound devices (HHUS) for point-of-care ultrasound (POCUS) to improve outpatient care in rural Brandenburg. Materials and Methods A group of general practitioners (n = 9), palliative care physicians (n = 6), emergency physicians (n = 4), and nurses from palliative care services (n = 5) participated in this study. Following a 3-hour workshop and 2 weeks of individual training, participants performed POCUS using HHUS (HH-POCUS). Indications, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 29 publications
1
16
0
3
Order By: Relevance
“…The quality of the included articles will be evaluated using the mixed method appraisal tool [ 23 ] version 2018 [ 24 ]. Using MMAT, the methodological quality of five categories of research will be appraised, which include the following: qualitative research, randomized controlled trials, nonrandomized studies, quantitative descriptive studies, and mixed methods studies.…”
Section: Methodsmentioning
confidence: 99%
“…The quality of the included articles will be evaluated using the mixed method appraisal tool [ 23 ] version 2018 [ 24 ]. Using MMAT, the methodological quality of five categories of research will be appraised, which include the following: qualitative research, randomized controlled trials, nonrandomized studies, quantitative descriptive studies, and mixed methods studies.…”
Section: Methodsmentioning
confidence: 99%
“…In our recently published HH-POCUS study [28], the most common findings in PC patients with dyspnea (n = 65) were a large amount of ascites (n = 28), followed by pleural effusion (n = 11) (▶ Fig. 1) and a combination of both pleural effusion and ascites (n = 9) (▶Fig.…”
Section: The Role Of Handheld Ultrasound In Palliative Care Patients ...mentioning
confidence: 97%
“…For example, it has been used in hospice and outpatient clinical settings to assess bladder volume before catheterization and degree of ascites before paracentesis, thereby saving patients an uncomfortable trip to the hospital or any unnecessary catheterization [23,27]. In a recently published study [28], we demonstrated the feasibility of using HH-POCUS as a bedside examination tool to assess some of the most common acute symptoms in palliative patients, such as pain, dyspnea, and nausea/vomi-ting during homecare visits by a group of general practitioners and PCPs. Considering the lack of physicians in rural regions of Germany predicted for 2030 with distances of more than 30-50 km to the nearest family practice or hospital, PCNs were included in this study.…”
Section: Interventionsmentioning
confidence: 99%
“…Handheld ultrasound devices have transformed the application of POCUS in the home-based palliative care setting. [1,20,21] Palliative care physicians should receive mandatory training in POCUS to enable diagnostic proficiency. This would need acquiring higher training, as well as improvised skill sets, along with overcoming the associated implementation barriers to effective clinical practice.…”
Section: Indian Journal Of Palliative Carementioning
confidence: 99%
“…Handheld ultrasound devices have transformed the application of POCUS in the home-based palliative care setting. [ 1 , 20 , 21 ]…”
Section: Introductionmentioning
confidence: 99%